Proposed business strategy of pt chandra asri petrochemical polyethylene product in indonesia - Goenawan, Rowan; Kartajaya, Hermawan (The Indonesian Journal of Business Administration, 2018)
Abstract - PT CAP Tbk is the largest publicly listed petrochemical company in Indonesia. Polyolefins plant produces Polyethylene (PE) and Polypropylene (PP). As of 2017, Indonesia is still a net importer country for PE. Indonesia can be described as the haven of imported materials simply because of stable domestic demand and insufficient domestic supply. And going forward, the condition is expected to remain in deficit and highly dependent on imports as long as there is no domestic plant expansion in the future. For PE, the domestic producers are only have two producers, which are PT Chandra Asri Petrochemical Tbk and PT Lotte Chemical Titan Nusantara Tbk.. The thesis is consisting of: internal analysis, external analysis, business strategy formulation, and implementation plan. In addition, business strategic recommendation would be provided for PT CAP Tbk. The objectives of this study is to provide the insightful information for the most potential resources from the company to grow the business as well as to formulate the best fitted business strategy for PT CAP Tbk in order to capture market opportunities in domestic PE business. As a result, based on SWOT analysis, the business strategies have been formulated, which consists of: production capacity expansion, geo-expansion, new product diversification, R&D collaboration, operational excellence, cost efficiency and effectiveness, human capital development, channel distribution management. The implementation plan would be divided on two phases, short term plan and long term. On short term, PT CAP Tbk should develop and execute marketing strategy for new product development and diversification. And for the long term, the new capacity expansion is worth to be executed in order to capture all the market opportunities in Indonesia PE business.Keywords: polyethylene, Chandra Asri Petrochemical, business strategy, strategy formulation, strategy implementation